Satisfaction with Life in High School Students from Arequipa [Satisfacción con la vida en escolares de la ciudad de Arequipa] - Arias Gallegos, Walter Lizandro (2018)
ABSTRACT This study, in the framework of the Positive Educational Psychology, has two objectives: to perform a psychometric analysis of the Satisfaction with Life Scale, and to compare the resulting values according to gender, age and educational institution, in a group of schoolers from the city of Arequipa. We worked with a sample of 872 students in the 4th and 5th year of high school, from five mixed and single-sex schools. Besides, 46.9% of this sample are male students and 53.1% are female students. The sample was obtained by probabilistic methods. The Diener’s Satisfaction with Life Scale was used. The outcomes indicate that the test has a one-dimensional factorial structure and suitable reliability for latent variables (ω= .99 and H= .99). The comparisons suggest that, male students and those who are older have higher levels of satisfaction with life.